2021
DOI: 10.1186/s12866-021-02215-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of gut microbiota of a healthy population and covariates affecting microbial variation in two large Japanese cohorts

Abstract: Background Inter-individual variations in gut microbiota composition are observed even among healthy populations. The gut microbiota may exhibit a unique composition depending on the country of origin and race of individuals. To comprehensively understand the link between healthy gut microbiota and host state, it is beneficial to conduct large-scale cohort studies. The aim of the present study was to elucidate the integrated and non-redundant factors associated with gut microbiota composition w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Nishijima et al [ 12 ] also demonstrated that the gut microbiome structure in a Japanese population was considerably different from that of other populations, with at least one of the differences being the rich abundance of the genus Bifidobacterium . Park et al [ 18 ] also described the high abundance of Bifidobacterium as a feature of the gut microbiota of 1596 healthy Japanese individuals. Thus, a high abundance of Bifidobacterium seems to be notable in the structure of Japanese gut microbiota, representign an important genus, independent of the presence or absence of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nishijima et al [ 12 ] also demonstrated that the gut microbiome structure in a Japanese population was considerably different from that of other populations, with at least one of the differences being the rich abundance of the genus Bifidobacterium . Park et al [ 18 ] also described the high abundance of Bifidobacterium as a feature of the gut microbiota of 1596 healthy Japanese individuals. Thus, a high abundance of Bifidobacterium seems to be notable in the structure of Japanese gut microbiota, representign an important genus, independent of the presence or absence of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic data in all patients were assessed using right heart catheterization. The control participants were selected from the database at the National Institutes of Biomedical Innovation, Health and Nutrition and matched with patients with CTEPH in terms of age, sex, and body mass index (BMI) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, several studies have aimed to elucidate gut microbiota in the healthy Japanese population and provided intriguing evidence regarding the average gut microbiota [ 14 , 15 , 17 , 18 ], although the numbers of subjects were relatively small compared with our study (367 [ 14 ], 516 [ 15 ], 277 [ 17 ] and 1,946 [ 18 ]). When comparing our results with those of previous studies, we found both consistency and inconsistency in our findings.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, elucidation of outlier gut microbiota may lead to the identification of hidden factors, including specific diseases. However, reports analyzing the gut microbiotas of healthy populations, especially the Japanese population, are limited, and the sample sizes have been too small [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%